Moving forward: business model solutions for amateur sport clubs. Issue 3 (4th May 2021) - Bradbury, Trish; Mitchell, Roger; Thorn, Kaye
ABSTRACT: Rationale/Purpose: The survival of New Zealand's amateur sport clubs is threatened by a range of factors. This study investigated how club partnerships may address sustainability concerns brought about through sport environmental changes. Design/Methodology/Approach: Semi-structured interviews with representatives from five sport clubs explored how partnerships could alter sport clubs' business models for long-term viability. Findings: Partnerships enabled clubs' governing bodies to appeal to a wider cross-section of society through improved strategic focus, direction and resource use. This led to membership growth and diversity, enhanced financial viability, improved governance, greater community connection and improved HRM functions. Practical Implications: The study suggests the RCOV model and RDT helped clubs' pre-partnership sustainability issues. Partnerships created larger clubs, enabling financial stability, retention of members, and resource management to overcome environmental challenges. Research Contribution: This study offers perceptions of club partnership outcomes. Critical success factors are presented as a guide of best practice.